Understanding Chinese high school students' Foreign Language Enjoyment: Validation of the Chinese version of the Foreign Language Enjoyment scale. (August 2018) - Li, Chengchen; Jiang, Guiying; Dewaele, Jean-Marc
Abstract: Scholarly attention for Foreign Language Enjoyment (FLE) has sharply increased in the past three years for its role in facilitating language learning as well as promoting language learners' well-being. However, the conceptualization and measurement of FLE in China, which has the largest number of EFL learners in the world, is only just starting. Adopting a mixed-method approach, the current study examined the psychometric properties of the Chinese Version of the Foreign Language Enjoyment Scale, and investigated FLE in a specific Chinese EFL context. Through surveying two samples of 1718 students and 360 students in Stages 1 and 2, a new 11-item and 3-factor model (i.e. FLE-Private, FLE-Teacher, and FLE-Atmosphere ) was confirmed and validated. The students scored highest on FLE-Teacher, followed by FLE-Private and FLE-Atmosphere . The analysis of the qualitative data collected from 64 participants in Stage 3 showed that beyond the general factors linked to the teacher and peers, the individual experience of FLE is shaped by a large range of learner-internal and learner-external variables.